Investigation of doping techniques on the silicon based capacitor / Ahmad Akmalhakim Yaacob - Yaacob, Ahmad Akmalhakim (2010)
This paper investigates the effect of doping techniques, type of dopant species and plate size on the capacitance density of a silicon based capacitor. The substrate of the silicon wafers were highly doped using either solid source (SS) or spin-on dopant (SOD) method. The wafers were doped according to their types where the n-type wafers were doped with phosphorus where as the p-type wafers were doped with boron. Three different diffusion temperatures were used in this experiment which are 900oC, 1000oC and 1050oC. The diffusion process was conducted by using the ModuLab diffusion furnace. The low-frequency CV measurement using the Keithley 595 Quasistatic CV meter was conducted in order to study the capacitance value in this research. Results show that the diffusion by spin-on dopant gives a higher capacitance density compared to diffusion by solid source and larger plate size would contribute to a larger capacitance value. In addition, the experiment also shows that n-type wafer heavily doped with phosphorus exhibits a higher capacitance density.